KERAGAMAN SPESIES DAN PERSEBARAN FAUNA ANURA DI CAGAR ALAM DAN TAMAN WISATA ALAM TELAGA WARNA - Wawan Setiawan; Wahyu Prihatini; Sri Wiedarti (Universitas Pakuan, 2019)
Anura includes frogs and toads, playing an important role as ecosystem quality bioindicators, as well as insect population control. Anura is very sensitive to changes in the environment, since its egg stadium. Disruption to its natural habitat, can threaten Anura's survival. This research is done in the Nature reserve area and Telaga Warna Natural Nature Park. Observations using the Visual Encounter Survey (VES) method. Analyses conducted include the calculation of the species diversity index of Shannon-Wienner, the frequency of species meetings, and the density of species. The results of the research gained 11 species of Anura from 5 families, namely Megophryidae, Microhylidae, Ranidae, Dicroglossidae, and Rhacoporidae. The level of diversity of Anura species in the research site is moderate (H ' = 0.152). Density ranged from 0.07 to 0.24 tails/m2, and the highest density is demonstrated by the Rhacophorus margaritifer. The frequency of meetings at a sampling location ranges from 0.01 to 3.6%, with the highest frequency being Rana chalconota. Generally, the quality of the ecosystem of Telaga Warna is good, especially in the area of Gayung Swamp